2008
DOI: 10.1785/0120080037
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependence of Coda Q, Part I: Numerical Modeling and Examples from Peaceful Nuclear Explosions

Abstract: Frequency-dependent coda attenuation values are often reported; however such measurements usually depend on the types of the Q(f) models employed. We use numerical modeling of Peaceful Nuclear Explosion (PNE) codas at far regional to teleseismic distances to compare two of such models, namely the conventional frequency-dependent Q coda (f) = Q 0 f  and frequency-independent coda attenuation (Q c ) with geometrical attenuation (). The results favor strongly the (, Q c ) model and illustrate the mechanisms le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…9a) were nearly identical to those independently measured from the data (Fig. 9c; Morozov et al 2006; Morozov et al 2008). The modelling used realistic layered lithospheric structures derived from detailed studies of this PNE line (Morozov et al 1998; Morozova et al 1999).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9a) were nearly identical to those independently measured from the data (Fig. 9c; Morozov et al 2006; Morozov et al 2008). The modelling used realistic layered lithospheric structures derived from detailed studies of this PNE line (Morozov et al 1998; Morozova et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…A more complete and rigorous theoretical treatment with additional examples using surface‐ body‐, and Lg waves are given by Morozov (2008). Coda (γ, Q e ) modelling results in realistic lithospheric structures are reported by Morozov et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Observed magnitude for the Kalpakkam and Patna is found to be 6.3 and 7.0, respectively, so this method cannot be applied to these SSA. Maximum magnitude estimation by coda (Q 0 ) (MM4) is given in Tables 5 and 6; Q 0 value for South India is found to be 460 (Mandal and Rastogi 1998;Morozov et al 2008), and it was concluded that South India is under the stable continental region in terms of Q 0 . An estimated coda wave for Himalayan range is M max varies from 4.5 to 7.5 for TFL diverges from 5.14 to 321.03 km M max varies from 4.5 to 7.5 for TFL diverges from 5.14 to 321.03 km NA not available a As per Table 1 varied from 1100 to 1200 (Kumar et al 2007).…”
Section: Maximum Magnitude (M Max ) Estimation By Existing Methodsmentioning
confidence: 98%
“…However, Edwards et al (2008Edwards et al ( , 2011 have shown that a frequency-dependent Q model might give a better spectral fit but can lead to a strong trade-off with the frequency-independent geometrical spreading parameter. Moreover, Morozov et al (2008) obtained a spurious frequency-dependent Q model with α ≈ 0:5 while using a frequency-independent Q for the input numerical simulations. Given that the goal of the present study is to derive an easily adjustable response spectral GMPE, a simple frequency-independent model for Q was considered.…”
Section: Determination Of Stochastic Ground-motionmentioning
confidence: 99%